Pengaruh Pengetahuan dan Perilaku Nasabah terhadap Keputusan Nasabah dalam Memilih Produk Tabungan Simpel (Simpanan Pelajar) di BPRS Lantabur Tebuireng Jombang: Studi Kasus PT. BPRS Lantabur Tebuireng Kantor Cabang Pelayanan Kas Cukir - Rizky Amalia, Alfy; Suselo, Dedi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of customer knowledge and behavior in choosing student savings at BPRS Lantabur Tebuireng, Cukir Cash Service Office. The data collection technique uses a questionnaire. The population of research subjects was 244 people with a total sample of 82 respondents using the Slovin sample. The type of research is quantitative. The data analysis techniques used include Validity Test, Reliability, Simple Linear Regression Test, Significant Test (t), and coefficient of determination (R2) using the Statistical Product and Service Solutions (SPSS) Version 21 program. The results of this study show that customer knowledge has no effect significant impact on decisions, while behavior has a positive and significant influence on customer decisions.